A Critical Genre Analysis in Food Promotion: Salad Advertising - Antonetta, Vinlie; Arianto, Shakira Dwi Azura; Sinar, Tengku Silvana (Universitas Pamulang, 2025)
This study applies Bhatia's Critical Genre Analysis (CGA) framework to analyze promotional posters from four salad brands—SaladPoint, SaladStop!, Hijoo Salad Bar, and The Roots. It examines how textual, visual, and interactive resources are integrated to communicate brand messages and engage health-conscious audiences effectively. By focusing on genre features like audience targeting, multimodal resources, and interdiscursivity, the study reveals how these strategies align with consumer priorities such as health, convenience, and lifestyle. The analysis shows that the brands use bold typography, vibrant imagery, and strategic calls to action to craft persuasive advertisements. Features like bright colors, fresh ingredients, and friendly language appeal to the health-conscious demographic, promoting a sense of ease and community. Interactive elements such as QR codes and social media handles further enhance consumer engagement. These multimodal strategies work cohesively to convey the brands' ethos and strengthen their appeal. The findings emphasize the importance of Bhatia’s CGA framework in understanding promotional communications, particularly in industries where consumer choices are shaped by perceptions of health, quality, and brand image. Effective advertisements must balance visual, verbal, and interactive elements to resonate with target audiences. This study offers actionable insights for optimizing advertising strategies in the competitive food industry, highlighting the need for cohesive multimodal approaches to boost consumer engagement and brand identity. It also contributes to broader discussions on multimodality and genre in advertising, providing a methodological framework for analyzing promotional materials